2021
DOI: 10.1097/eja.0000000000001505
|View full text |Cite
|
Sign up to set email alerts
|

Intra-operative nociceptive responses and postoperative major complications after gastrointestinal surgery under general anaesthesia

Abstract: BACKGROUND Surgical procedures stimulate nociception and induce physiological responses according to the balance between nociception and antinociception. The severity of surgical stimuli is associated with major postoperative complications. Although an intra-operative quantitative index representing surgical invasiveness would be useful for anaesthetic management to predict and prevent major complications, no such index is available. OBJECTIVES To ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
(99 reference statements)
0
8
1
Order By: Relevance
“…Our previous study showed that a higher degree of surgical invasiveness increases mean NR index during surgery, associating with a higher incidence of postoperative morbidity 19 24. In the present study, however, mean NR≥0.83 was not selected as independent risk factors for major complications after P/D for MPM in the present study.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Our previous study showed that a higher degree of surgical invasiveness increases mean NR index during surgery, associating with a higher incidence of postoperative morbidity 19 24. In the present study, however, mean NR≥0.83 was not selected as independent risk factors for major complications after P/D for MPM in the present study.…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, we previously reported that mean NR index during laparoscopic gastrointestinal surgery was 0.815±0.053, and the incidence of major complications was 8.2% 25. Moreover, after we recalculated mean NR index using our previous data, mean NR values were 0.817±0.057 during gastrointestinal surgery including laparotomy and laparoscopic surgery and 0.818±0.056 during total shoulder arthroplasty, and the incidences of major postoperative complications were 14.5% and 1.2%, respectively 19 26. Since mean NR index during P/D corresponds to the highest level of surgical severity even in patients with epidural block,24 it might be plausible that multivariable logistic regression analyses did not select mean NR≥0.83 as independent risk factors for major complications in the present study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Results from nociception monitors combining these autonomic responses are thus also expected to be associated with postoperative complications. Higher values of NR averaged from the start to the end of surgery (mean NR), which are calculated using heart rate, systolic blood pressure, and peripheral perfusion index, were reportedly associated with a higher incidence of major postoperative complications, defined as a Clavien–Dindo Class ≥ IIIa, after gastrointestinal surgery ( Table 1 ) [ 44 ]. Mean NR values also increased in the order of severity of postoperative complications in patients undergoing total shoulder arthroplasty, gastrointestinal surgery, and thoracic surgery ( Figure 2 ) [ 44 , 45 , 46 , 84 , 85 ].…”
Section: Nociception Monitors and Postoperative Complicationsmentioning
confidence: 99%
“…Gray circles show individual data points. Data in this graph were obtained from [ 44 , 45 , 46 , 84 , 85 ]. Significant differences are defined at * p < 0.001 vs. no complications, and # p < 0.001 vs. minor complications.…”
Section: Figurementioning
confidence: 99%